An amplitude variation Field subtraction technique for visualization of vasculature of the human eye. (September 2019) - Basu, Mainak; Poddar, Raju
Highlights: A new method Amplitude Variation Field Subtraction (AVFS) is reported to analyze optical coherence tomography (OCT) image. The method is utilized for visualization and generation of angiography image of human retina. AVFS is compared with other two methods namely Phase Variance and Speckle Variance. Two new ultra-speed OCT imaging platform is described. The angiography images generated from AVFS is free from the flawed phase jumps compared with Phase Variance method. Abstract: Optical Coherence Tomography (OCT) and angiography is widely considered as a significant achievement for non-invasive bio-medical imaging which have also been used for visualization of microstructure and microvasculature of tissue, noninvasively. This makes use of class of algorithmic technique which fall under the domain of optical coherence tomography angiography (OCTA), which includes the use of mainly phase variance, Doppler, and speckle variance. Despite some inherent advantages, many of these algorithms, namely phase variance and speckle variance suffer from certain drawbacks, which necessitates post-processing of the generated image, thereby incurring a chance for the loss of information. In this article, we propose an alternative iterative technique based on amplitude variance subtraction, which can be used in an independent manner to visualize the blood vessels. Results shown are comparable in their nature with existing phase variance and speckle variance methods but without the requirement of any additional filters or post-processing and is also free from the erroneous phase jumps and phase stabilization.